Tapeworms (Cestoda: Caryophyllidea), parasites of Clarias batrachus (Pisces: Siluriformes) in the Indomalayan region - Ash, Anirban; Scholz, Tomáš; Oros, Mikuláš; Kar, Pradip Kumar (The Journal of parasitology, 2011)
Revision of monozoic cestodes (Caryophyllidea) parasitic in commercially important walking catfish Clarias batrachus (L.) in tropical Asia (Indomalayan zoogeographical region) was carried out, based on the evaluation of newly collected material from India, Indonesia, and Thailand, as well as a study of type specimens. Instead of the 59 nominal taxa of 15 genera from 3 caryophyllidean families previously described, only 8 species of the Lytocestidae are considered to be valid: Bovienia indica (Niyogi, Gupta and Agarwal, 1982) n. comb.; Bovienia raipurensis (Satpute and Agarwal, 1980) Mackiewicz, 1994; Bovienia serialis (Bovien, 1926) Fuhrmann, 1931; Djombangia penetrans Bovien, 1926; Lucknowia microcephala (Bovien, 1926) n. comb.; Lytocestus indicus (Moghe, 1925) Woodland 1926; Pseudocaryophyllaeus ritai Gupta and Singh, 1983; and Pseudocaryophyllaeus tenuicollis (Bovien, 1926) n. comb. All valid species are redescribed and SEM photomicrographs of their scolices and photomicrographs of their eggs are provided for the first time. Crescentovitus Murhar, 1963, Heeradevina Srivastav and Khare, 2005, Pseudobatrachus Pathak and Srivastav, 2005, Pseudobilobulata Srivastav and Lohia, 2002, Pseudoclariasis Pathak, 2002, and Pseudoinverta Pathak, 2002 are invalidated and 50 nominal species are newly synonymized, including 4 species described from other fish hosts. Taxonomic status of the remaining caryophyllidean taxa reported from C. batrachus (at least 6 taxa) could not be clarified because of the unavailability of their original descriptions. A key to identification of caryophyllidean tapeworms parasitic in C. batrachus is provided. To avoid current inflation of descriptions of invalid taxa, researchers are strongly encouraged to work only with well-fixed material; damaged, decomposed, or strongly flattened specimens should not be used for taxonomic studies, and type specimens must always be deposited in internationally recognized collections.
Keywords: nemoci ryb; jihovýchodní Asie; Animals; Catfishes; India; sumci; Asia, Southeastern; Fish Diseases; Cestode Infections; zvířata; Indie; cestodózy; Cestoda